Biomarkers of folate status in NHANES: a roundtable summary 1-6 - MOLLOY, ANNE MARIE (My University, 2011)
A roundtable to discuss the measurement of folate status biomarkers in NHANES took place in July 2010. NHANES has measured serum folate since 1974 and red blood cell (RBC) folate since 1978 with the use of several different measurement procedures. Data on serum 5-methyltetrahydrofolate (5MTHF) and folic acid (FA) concentrations in persons aged ?60 y are available in NHANES 1999?2002. The roundtable reviewed data that showed that folate concentrations from the Bio-Rad Quantaphase II procedure (Bio-Rad Laboratories, Hercules, CA; used in NHANES 1991?1994 and NHANES 1999?2006) were, on average, 29% lower for serum and 45% lower for RBC than were those from the microbiological assay (MA), which was used in NHANES 2007?2010. Roundtable experts agreed that these differences required a data adjustment for time-trend analyses. The roundtable reviewed the possible use of an isotope-dilution liquid chromatography?tandem mass spectrometry (LC-MS/MS) measurement procedure for future NHANES and agreed that the close agreement between the MA and LC-MS/MS results for serum folate supported conversion to the LC-MS/MS procedure. However, for RBC folate, the MA gave 25% higher concentrations than did the LC-MS/MS procedure. The roundtable agreed that the use of the LC-MS/MS procedure to measure RBC folate is premature at this time. The roundtable reviewed the reference materials available or under development at the National Institute of Standards and Technology and recognized the challenges related to, and the scientific need for, these materials. They noted the need for a commutability study for the available reference materials for serum 5MTHF and FA.
PUBLISHED
Keywords: Nutrition